2020
DOI: 10.1093/mnras/staa1122
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the tidal scars of the Small Magellanic Cloud

Abstract: Due to their close proximity, the Large and Small Magellanic Clouds (LMC/SMC) provide natural laboratories for understanding how galaxies form and evolve. With the goal of determining the structure and dynamical state of the SMC, we present new spectroscopic data for ∼ 3000 SMC red giant branch stars observed using the AAOmega spectrograph at the Anglo-Australian Telescope. We complement our data with further spectroscopic measurements from previous studies that used the same instrumental configuration as well… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 128 publications
2
11
0
1
Order By: Relevance
“…We modelled the centre-of-mass motion of the SMC using a Bayesian approach, assuming three different positions for the centre of the galaxy that are commonly used in the literature and found the following: (μ W,H I , μ N,H I ) = (−0.800 ± 0.027, −1.195 ± 0.012) mas yr −1 for the H I centre, (μ W, optical , μ N, optical ) = (−0.743 ± 0.027, −1.233 ± 0.012) mas yr −1 for the optical centre and (μ W, Cepheid , μ N, Cepheid ) = (−0.734 ± 0.027, −1.237 ± 0.012) mas yr −1 for the Cepheid centre. Our values agree best with the recent determinations from Gaia Collaboration (2018a), Zivick et al (2018), andDe Leo et al (2020) using space-based data. We also presented spatially resolved maps of the absolute and residual PMs of likely SMC member stars and analysed the internal motions of the intermediate-age/old and young stellar populations within the SMC.…”
Section: S U M M a Ry A N D C O N C L U S I O N Ssupporting
confidence: 92%
See 2 more Smart Citations
“…We modelled the centre-of-mass motion of the SMC using a Bayesian approach, assuming three different positions for the centre of the galaxy that are commonly used in the literature and found the following: (μ W,H I , μ N,H I ) = (−0.800 ± 0.027, −1.195 ± 0.012) mas yr −1 for the H I centre, (μ W, optical , μ N, optical ) = (−0.743 ± 0.027, −1.233 ± 0.012) mas yr −1 for the optical centre and (μ W, Cepheid , μ N, Cepheid ) = (−0.734 ± 0.027, −1.237 ± 0.012) mas yr −1 for the Cepheid centre. Our values agree best with the recent determinations from Gaia Collaboration (2018a), Zivick et al (2018), andDe Leo et al (2020) using space-based data. We also presented spatially resolved maps of the absolute and residual PMs of likely SMC member stars and analysed the internal motions of the intermediate-age/old and young stellar populations within the SMC.…”
Section: S U M M a Ry A N D C O N C L U S I O N Ssupporting
confidence: 92%
“…Our results, for the same SMC centre, are consistent with the findings of Zivick et al (2018) and are just outside the 1σ limit of the measurements by Gaia Collaboration (2018b). Recently, De Leo et al (2020) studied in detail the kinematics within the SMC using spectroscopic data as well as PM data from Gaia DR2. The value they found for the SMC bulk motion using the position of the optical SMC centre is consistent within 2σ with our result, adopting the same centre.…”
Section: Comparison With the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The lower-left panel of Figure 15 shows there to be significant dispersion in M1, precisely at the SMC edge of enhanced proper motion and at the LMC-SMC interface, where a mixture of Cloud populations is to be expected. The SMC is known to be disrupting (see, e.g., Zivick et al 2018;De Leo et al 2020) and the perturbed motions we observe here are likely a result of this, with the LMC violently dragging the eastern edge of the SMC toward it. The fact that we observe this signature in all three of the top panels indicates that the disruption is severe, penetrating through to the more centrally concentrated metalrich giants in M3.…”
Section: Slicing the Clouds By Metallicitymentioning
confidence: 80%
“…Recent studies which analysed the internal proper motion structure of the SMC (e.g. Oey et al 2018;Zivick et al 2018;De Leo et al 2020);Niederhofer et al 2020) found that stars east of the main body of the galaxy move preferentially away from the SMC, towards the East. This motion has been interpreted as a signature of tidal stripping of the outer parts of the SMC.…”
Section: D Structurementioning
confidence: 99%